2020
DOI: 10.1021/acs.jpcc.9b10055
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Spontaneous Charge Transfer at Metal/Organic Hybrid Heterostructures

Abstract: Hybrid materials are crucial in photovoltaics where the overall efficiency of the heterostructure is closely related to the level of charge transfer at the interface. Here, using various metal / poly(3hexylthiophene)(P3HT) heterostructure models, we reveal that the level of spontaneous charge transfer and electronic coupling at these interfaces depend on the conformational regularity of the organic polymer deposited on the metal substrate. Using ab-initio quantum chemical calculations based on density function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
3
0
3
Order By: Relevance
“…Furthermore, Özçelik et al combined DFT calculations with HD-VSFG measurements and obtained information about the interplay between molecular ordering/orientation and interfacial charge transfer. [52] It was observed that an increase in the regio-randomness (geometrical regio-randomness was intro- duced when the alkyl side chains were attached to the back bone from random locations in alternating monomers) of P3HT translates into an inefficient interlayer charge transfer, which is evident from the HD-VSFG measurements by correlating the intensity of the non-resonant contribution with the level of charge transfer. [52] These studies underline the potential of HD-VSFG to yield insights into function-determining processes in materials for efficient photovoltaic systems.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Özçelik et al combined DFT calculations with HD-VSFG measurements and obtained information about the interplay between molecular ordering/orientation and interfacial charge transfer. [52] It was observed that an increase in the regio-randomness (geometrical regio-randomness was intro- duced when the alkyl side chains were attached to the back bone from random locations in alternating monomers) of P3HT translates into an inefficient interlayer charge transfer, which is evident from the HD-VSFG measurements by correlating the intensity of the non-resonant contribution with the level of charge transfer. [52] These studies underline the potential of HD-VSFG to yield insights into function-determining processes in materials for efficient photovoltaic systems.…”
Section: Methodsmentioning
confidence: 99%
“…Dies ist aus den HD-SFS-Messungen ersichtlich, indem die Intensität des NR Beitrags mit dem Grad des Ladungstransfers korreliert wird. [52] Die vorgestellten Studien unterstreichen das Potenzial von HD-SFS, Einblicke in funktionsbestimmende Prozesse in Materialien für effiziente Photovoltaiksysteme zu gewinnen. Sie konzentrierten sich auf Veränderungen beim Ladungstransfer zwischen Goldsubstraten und P3HT-Adsorbaten in Abhängigkeit von der Polarisation des Anregungspulses.…”
Section: Strategien Für Eine Isolierteunclassified
“…Des Weiteren kombinierten Özçelik et al DFT-Berechnungen mit HD-SFS-Messungen und erhielten Informationen über das Zusammenspiel zwischen molekularer Ordnung/Orientierung und Ladungstransfer an der Grenzfläche. [52] Es wurde beobachtet, dass eine Zunahme von nicht regioregularen Bereichen (diese geometrischen Bereiche wurden eingeführt, als die Alkylseitenketten an zufälligen Stellen der alternierenden Monomere an das Rückgrat angebracht wurden) von P3HT zu einem ineffizienten Ladungstransfer zwischen den Schichten führt. Dies ist aus den HD-SFS-Messungen ersichtlich, indem die Intensität des NR Beitrags mit dem Grad des Ladungstransfers korreliert wird.…”
Section: Strategien Für Eine Isolierteunclassified
“…Hybrid heterostructures involving organic material thin films on inorganic substrates demonstrate unique properties which are radically different from their isolated components [1,2]. For appropriately chosen materials, the interfacial electrical, magnetic and optical properties can be engineered to realize new device functionalities, with many applications in organic electronics including light-emitting diodes, field-effect transistors, and solar cells [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%